[Pyr1]Apelin-13(1–12) Is a Biologically Active ACE2 Metabolite of the Endogenous Cardiovascular Peptide [Pyr1]Apelin-13 - Yang, Peiran; Kuc, Rhoda E.; Brame, Aimée L.; Dyson, Alex; Singer, Mervyn; Glen, Robert C.; Cheriyan, Joseph; Wilkinson, Ian B.; Davenport, Anthony P.; Maguire, Janet J. (Frontiers in Neuroscience, 2017)
Aims: Apelin is a predicted substrate for ACE2, a novel therapeutic target. Our aim was to demonstrate the endogenous presence of the putative ACE2 product [Pyr1]apelin-13(1-12) in human cardiovascular tissues and to confirm it retains significant biological activity for the apelin receptor in vitro and in vivo. The minimum active apelin fragment was also investigated. Methods and Results: [Pyr1]apelin-13 incubated with recombinant human ACE2 resulted in de novo generation of [Pyr1]apelin-13(1-12) identified by mass spectrometry. Endogenous [Pyr1]apelin-13(1-12) was detected by immunostaining in human heart and lung localized to the endothelium. Expression was undetectable in lung from patients with pulmonary arterial hypertension. In human heart [Pyr1]apelin-13(1-12) (pKi = 8.04±0.06) and apelin-13(F13A) (pKi = 8.07±0.24) competed with [125I]apelin-13 binding with nanomolar affinity, 4-fold lower than for [Pyr1]apelin-13 (pKi = 8.83±0.06) whereas apelin-17 exhibited highest affinity (pKi = 9.63±0.17). The rank order of potency of peptides to inhibit forskolin-stimulated cAMP was apelin-17 (pD2 = 10.31±0.28) > [Pyr1]apelin-13 (pD2 = 9.67±0.04)  apelin-13(F13A) (pD2 = 9.54±0.05) > [Pyr1]apelin-13(1-12) (pD2 = 9.30±0.06). The truncated peptide apelin-13(R10M) retained nanomolar potency (pD2 = 8.70±0.04) but shorter fragments exhibited low micromolar potency. In a β-arrestin recruitment assay the rank order of potency was apelin-17 (pD2 = 10.26±0.09) >> [Pyr1]apelin-13 (pD2 = 8.43±0.08) > apelin-13(R10M) (pD2 = 8.26±0.17) > apelin-13(F13A) (pD2 = 7.98±0.04)  [Pyr1]apelin-13(1-12) (pD2 = 7.84±0.06) >> shorter fragments (pD2<6). [Pyr1]apelin-13(1-12) and apelin-13(F13A) contracted human saphenous vein with similar sub-nanomolar potencies and [Pyr1]apelin-13(1-12) was a potent inotrope in paced mouse right ventricle and human atria. [Pyr1]apelin-13(1-12) elicited a dose-dependent decrease in blood pressure in anaesthetized rat and dose-dependent increase in forearm blood flow in human volunteers. Conclusions: We provide evidence that ACE2 cleaves [Pyr1]apelin-13 to [Pyr1]apelin-13(1-12) and this cleavage product is expressed in human cardiovascular tissues. We have demonstrated biological activity of [Pyr1]apelin-13(1-12) at the human and rodent apelin receptor in vitro and in vivo. Our data show that reported enhanced ACE2 activity in cardiovascular disease should not significantly compromise the beneficial effects of apelin based therapies for example in PAH.